Development of in-situ high-voltage and high-temperature stressing capability on atomic force microscopy platform. (December 2017) - Xiao, Chuanxiao; Jiang, Chun-Sheng; Johnston, Steve; Yang, Xiaowu; Ye, Jichun; Gorman, Brian; Al-Jassim, Mowafak
Graphical abstract: Highlights: In-situ stressing capability on AFM. Accelerated life test for solar cells. Monitor potential-induced degradation process. Evolution of the electrical potential with nm resolution. Abstract: Reliability has become an increasingly important issue as photovoltaic technologies mature. However, researching reliability at the nanometer scale is in its infancy; in particular, in-situ studies have not been reported to date. Here, to investigate potential-induced degradation (PID) of solar cell modules, we have developed an in-situ stressing capability with applied high voltage (HV) and high temperature (HT) on an atomic force microscopy (AFM) platform. We designed a sample holder to simultaneously accommodate 1000-V HV and 200 °C HT stressing. Three technical challenges have been overcome along with the development: thermal drift at HT, HV interference with measurement, and arc discharge caused by HV. We demonstrated no observable measurement artifact under the stress conditions. Based on our in-situ stressing AFM, Kelvin probe force microscopy potential imaging revealed the evolution of electrical potential across the junction along with the PID stressing time, which provides vital information to further study the PID mechanism.